HEUTAGOGI SEBAGAI PENDEKATAN PELATIHAN BAGI GURU DI ERA REVOLUSI INDUSTRI 4.0 - Rohmat Sulistya (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2019)
The role of teachers in the era of the industrial revolution 4.0 is not only as a giver of knowledge, but also as a life-long learners, learning leaders, instructors of learning resources, network former, and communication opener. These roles are inseparable from the demands of rapid change in all areas. Therefore, to adjust with the rapid changes, teachers must learn all the time throughout life. To achieve these roles, it is important to design about such updating teacher competencies’ training approaches that fit to the challenges of the 21st century. This study aims (1) to reveal the challenges of the industrial revolution 4.0 for teachers; and (2) offers the heutagogical approach to teacher training along with the outline its implementation steps. The study was carried out by analysing literatures comprehensively, referring to books, journals, and conference articles to answer the objectives of the study. The results of the study revealed that: (1) teachers faced major challenges to present interesting learning that fit with the conditions of millennial students and the challenge of responding to learning issues related to behavior, methods, and learning processes; (2) training programs with heutagogical approach need to be considered because it is a self-determined learning and and its implementation steps is by strengthening HOTS (Higher Order Thinking Skills) learning, strengthening digital literacy, developing a complete and reliable learning management system platform, and implementing teacher training with a heutagogy approach. To conlude, it is hoped that heutagogy can be an alternative approach of teachers training to produce teachers who are prepared for industrial revolution 4.0 learning challenges.AbstrakPeran guru di era revolusi industri 4.0 tidak hanya sebagai pemberi ilmu, tetapi juga sebagai pembelajar sepanjang hayat, pemimpin pembelajaran, pengarah sumber belajar, pembentuk jaringan, dan pembuka komunikasi. Peran-peran tersebut ini tidak terlepas dari tuntutan perubahan yang sangat cepat di segala ranah. Oleh karena itu, guru harus belajar sepanjang hayat untuk menyesuaikan dengan perubahan. Untuk mencapai peran ini, pemutakhiran kompetensi guru melalui pendekatan pelatihan yang sesuai tantangan abad 21 perlu diwujudkan. Kajian ini bertujuan untuk (1) mengungkapkan tantangan revolusi 4.0 bagi guru; dan (2) menawarkan pendekatan heutagogi dalam pelatihan guru beserta garis besar langkah implementasinya. Kajian dilakukan dengan studi literatur dan menganalisnya secara komprehensif, merujuk pada buku, jurnal, dan artikel konferensi untuk menjawab tujuan kajian. Hasil kajian mengungkapkan: (1) guru menghadapi tantangan besar untuk menghadirkan pembelajaran yang menarik dan selaras dengan kondisi peserta didik milenial dan tantangan untuk merespon isu-isu pembelajaran yang berkaitan dengan perilaku, metode, dan proses pembelajaran; (2) program pelatihan dengan pendekatan heutagogi perlu dipertimbangkan karena bersifat self-determined learning dengan langkah implementasi melalui penguatan pembelajaran HOTS, penguatan literasi digital, pengembangan platform learning management system yang lengkap dan handal, serta penerapan pelatihan guru dengan pendekatan heutagogi. Oleh sebab itu, heutagogi dapat menjadi alternatif pendekatan pelatihan guru untuk menghasilkan guru yang sadar akan peran pentingnya pada pembelajaran era revolusi industri 4.0.